Pemodelan Perubahan Tataguna Lahan Terhadap Debit Banjir DAS Tanggul, Jember Menggunakan Model SWAT (Soil and Water Assessment Tool) - Ainunisa, Diah; Halik, Gusfan; Widiarti, Wiwik Yunarni (Rekayasa Sipil, 2020)
Population growth is one of the causes of land-use change that can increase runoff. Tanggul watershed is one of the watersheds which often overflows during the rainy season. This study purpose to analyze the effect of land-use changes on runoff in Tanggul watershed using SWAT (Soil and Water Assessment Tool) model. To make sure the performance of SWAT model calibration and classified by the value of NSE and R2. The result of calibration included in a good category and validation included in a very good category. This study was modeling forest land-use change in 2004-2017 to determine the effect of land-use change on runoff. The result in this model of forest land-use change can increase runoff.